Economic relationship between child labour, poverty, school enrolment and economic growth in developing countries - Abdullahi, Idris Isyaku (2016)
This thesis provides empirical studies on important issues concerning child labour in developing countries. It aims at contributing to the literature on (1) the impact of poverty on the prevalence of child labour, (2) the effect of child labour prevalence on the rate of school enrolment and (3) the child labour impact on the economic growth. These objectives were achieved using both Difference generalised method of moments (D-GMM) and system generalised method of moments (S-GMM) estimators. The first objective evaluate the extent to which poverty of parents explains the prevalence of child labour in 55 developing countries and found that poverty is positively related to child labour prevalence in selected developing countries. This is an indication that increase in the level of household’s poverty tends to stimulate the extent of children participation in employment prematurely in the countries selected for the study. The second objective examined the impact of child labour on school enrolment as an important yardstick determining human capital development in 57 developing countries. The finding indicated that children participation in labour activities, results to decrease in the rate of their enrolment in schools, an action which consequently affects human capital development in the affected countries. Lastly, the third objective assess the influence of child labour in stimulating economic growth of 56 developing countries. Existence of an inverted U shape relation i.e. ‘growth child labour Kuznets’ curve was established between child labour and economic growth. This signifies that at the initial level of development of the countries studied, increase in child labour prevalence up to about 1.273 percent tends to positively stimulates growth of the selected developing countries. However any further increase in child labour prevalence beyond the threshold value of 1.273 percent, eventually leads to a decrease in the economic growth of the sample countries. The selection of sample countries to achieve the three objectives was based on the evidence of the existence of child labour in the developing countries studied and the study period was from 2009 to 2013. It was recommended that policies and programmes aimed at poverty alleviation should be pursued vigorously by governments of the developing countries so as to deter the chances of parent engaging their children in child labour. Similarly, flexible school system should be encourage to allow children some liberty to engage in works particularly after school hours or during holidays. This will in a away leads to improvement in the rate at which children enrolled in schools, so as to provide necessary improvement in human capital development which is seen as a necessary stimulant of economic growth. Lastly, governments of developing countries should strive to ensure that child labour prevalence did not exceed the threshold level, as this could impede their economic growth.